Application of Google Meet’s Synchronous Learning and Asychronous E-Learning on Learning Effectiveness - Meriyati Meriyati; Romlah; Eti Hadiati; Agus Jatmiko (Dinasti International Journal of Education Management And Social Science, 2023)
Application of Google Meet's Synchronous Learning and Asynchronous E-Learning to Learning Effectiveness is a scientific article of literature study within the scope of Education Management science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects are sourced from online libraries, Google Scholar, Mendeley and other academic online media. Library research methods, from e-books and open access e-journals. The results of this study are: 1) Google Meet Synchronous Learning has an effect on Learning Effectiveness; 2) Asynchronous Learning E-Learning influences Learning Effectiveness; and 3) Google Meet Synchronous Learning affects E-Learning Asynchronous Learning.